Environmental Management Practices amongst Tobacco Farmers in Migori County, Kenya - , Lydia Boke Marwa; , Jacob K. Kibwage; , Godfrey W. Netondo (Archives of Current Research International, 2017)
Aim: To assess environmental management practices carried out by both tobacco farmers and companies. Methodology: Purposive sampling was employed for data collection where by tobacco farmers were randomly selected from the population. Sub-county Forest Officer and two field officers from Kenya Forest Service were also interviewed. Results: Use of improved barn is among the environmental management practices that can reduce deforestation because of its high thermal efficiency. However, only 22% of the respondents used improved barn while 78% used traditional barn which is non-energy saving barn, therefore consuming tonnes of wood compared to improved barns. The study showed that 97.7% of the respondents had not been advised by tobacco companies to use any other method to control pests except chemical pesticides. Of the respondents, 97.1% believed tobacco companies did not promote alternative source of energy for curing tobacco other than wood. Conclusion: Although not much was being done, farmers had adopted a few practices to prevent soil and forest degradation. Most of the soil management practices and alternative curing technologies were non-existent in the study area and tobacco companies were yet to introduce them and this had greatly compromised the status of the environment. Use of chemical pesticides was on a large scale in the study area. Some of the efforts by tobacco companies employed to mitigate the environmental impacts were promoting reforestation and appropriate use of fertilizers and pesticides. The very few existing environmental management practices carried out by few tobacco farmers and tobacco companies were not adequate to mitigate the negative impacts caused by tobacco farming.